The Effectiveness of Trashbags in the Merdeka Sampah Action with Disabled Persons as a Manifesto of the East Java Nasyiatul Aisyiyah Inclusive Movement - Zahrotul Janah (Yayasan Multidimensi Kreatif, 2024)
Waste is one of the pressing environmental problems in Indonesia, with waste generation in East Java reaching 16,759 tons per day (SIPSN, 2024). Public awareness of the importance of waste segregation still needs to be increased. The Waste Freedom Movement with people with disabilities by Nasyiatul Aisyiyah East Java is an inclusive, innovative solution, involving the disabled community in education about waste sorting through colored trash bags (yellow, blue, green and red). This research aims to measure the effectiveness of trash bags as an educational medium and explore the challenges and opportunities of this inclusive environmental movement. The research was conducted in 8 districts/cities in East Java using qualitative methods, involving the disabled community and Special Schools (SLB). The results of this research showed that 90.9% of respondents strongly agreed that Trashbag made the educational process of sorting waste easier for people with disabilities, as many as 81.8% of respondents stated that they strongly agreed that flexible waste sorting Trashbags were used as an educational medium in various places, and 81.8% of respondents strongly agreed that the activity of sorting waste using waste sorting Trashbags for people with disabilities was a representation of manifesto of the East Java Nasyiatul Aisyiyah inclusive movement.